PENGARUH KEPUASAN KERJA DAN MOTIVASI BERPRESTASI TERHADAP KINERJA MANAJERIAL DIMEDIASI KOMITMEN AFEKTIF PADA KEJAKSAAN TINGGI WILAYAH KALIMANTAN TIMUR - Adhitia Ferdinand Ideris; Tetra Hidayati; Ariesta Heksarini (Universitas Pamulang, 2021)
The purpose of this study is to test the influence between job satisfaction and motivation of achievement on managerial performance with affective commitment as an intervening variable in Kejaksaan Tinggi Kalimantan Timur area. This research is classified as quantitative research that is expected to measure the influence between variables. Data collection was conducted using questionnaires with sampling techniques are saturated samples, as many as 60 respondents. Data processing is done using SEM (Structural Equation Modelling). The results of this study showed that job satisfaction, performance motivation and affective commitment each had a significant positive effect on managerial performance. The results of the analysis also showed that affective commitment mediates the indirect influence between job satisfaction and the motivation of achievement on managerial performance and the nature of partial mediation. The meaning of this research is that the better employee job satisfaction and the higher the motivation of employee achievement, the higher the affective commitment that will further improve employee performance.